2017
DOI: 10.1186/s40886-017-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Why adopt ISO 9001 certification in hospitals? A case study of external triggers and sensemaking in an emergency department in Norway

Abstract: Background: Certification and accreditation are widely used to achieve quality and safety in health care but are also questioned regarding their assumed effects. This is a challenge for policymakers and managers, since adoption of these regimes can have a circumstantial impact upon organizations. This study's aim was to explore how external conditions catalyzed and triggered organizational change and internal sensemaking processes as part of an ISO 9001 certification process. Methods: The study applied an expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Further, the auditing practices inside hospital departments showed examples of the possibilities the auditors had to uncover challenges or opportunities for improvement of daily activity. Such practices can give surprises or external disruptions leading hospitals to trigger resilience by activating internal collective sensemaking processes and purposeful reorganizing [46][47][48].…”
Section: Certification As Support For Resilient Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Further, the auditing practices inside hospital departments showed examples of the possibilities the auditors had to uncover challenges or opportunities for improvement of daily activity. Such practices can give surprises or external disruptions leading hospitals to trigger resilience by activating internal collective sensemaking processes and purposeful reorganizing [46][47][48].…”
Section: Certification As Support For Resilient Performancementioning
confidence: 99%
“…We also found that auditors empowered local improvement initiatives at the sharp end. A holistic approach to auditing has been shown to be important for internal motivation and commitment to auditing practice and improvement work [18,48]. The potential to learn is also exposed when auditors take initiatives to transfer experiences and good practices from one auditee to another, within or between organizational fields.…”
Section: The Potential To Learnmentioning
confidence: 99%
“…According to recent studies there is an ongoing turning point in the context of accreditation: moving from a culture of means towards evaluation of results, addressing the organizational core (Brubakk et al. , 2015; Johannesen and Wiig, 2017; Johannesen et al. , 2020; Johannesen, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of our paper, the analysis of the impact of the application of ISO standards on financial performance in private hospitals, we selected the following papers. Johannesen et al [8] pointed out the reasons for the application of ISO standards in hospitals (such as Norway). Chaw et al [3] identify key differences in quality management between accredited hospitals, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By adhering to the standard, health institutions improve the efficiency of a management system and thus strengthen the trust that their patients have in their system [24]. By certifying the management system, health institutions can show their readiness to consistently comply with all the requirements of the standard aiming to constantly improve patient satisfaction which is reflected in improving their health by providing quality health care [8]. Health is a basic human right and one of the most important prerequisites for economic development and quality life of inhabitants of a country [14, p. 168].…”
Section: Characteristics Of Iso Standards and Their Application In Pr...mentioning
confidence: 99%